Foliar treatments of Sugar beet - Ungai, Diána; Széles, Éva; Győri, Zoltán (Acta Agraria Debreceniensis, 2007)
The yield and quality of the sugar beet are mainly determined by the plant production system, thus we studied the effect of mineral fertilization. Our field trials were carried out in 2005 and 2006 in Hajdúböszörmény, at two sites. We studied the effect of sulphur (Cosavet DF), copper (Kelcare Cu) and two foliar nutrients with high active agents. Treatments were replicated four times. We took root and leaf samples at 4 week intervals, starting in August. The quality of root (sucrose, potassium, sodium and alfaamino N content) was determined from filtrated beet broth, by an automatic beet laboratory system, called VENEMA. Leaf samples were measured with ICP-OES. We found that the crop and the sugar yield were significantly influenced by the foliar treatments.